Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I was doing practice exercise for differential equations and couldn't wrap my head around this one:


We need to find a differential equation that $y$ satisfies and the $ODE$ should not contain any constants. If the $C_1$ was outside $\sin$, then the answer would be much easier. I tried using different identities, inlcuding: $$\sin(x + y) = \sin(x)\cos(y) + \cos(x)\sin(y)$$ $$\cos(x + y) = \cos(x)\cos(y) - \sin(x)\sin(y)$$

But I just could not eliminate the constant because it is inside $\sin$. Any tips would be much appreciated.

share|cite|improve this question
Differentiate twice... – copper.hat Feb 16 '14 at 17:13
But it only has one constant, doesn't it mean the differential equation is only first-order, hence only differentiate once? – SomeGuyOutThere Feb 16 '14 at 17:15
How about $y'=\sqrt{1-y^2}$? – Artem Feb 16 '14 at 17:20
up vote 4 down vote accepted

$$y=\sin(x+c)\implies y'=\cos(x+c) \implies y''=-\sin(x+c) \implies y''+y=0$$

share|cite|improve this answer

For this problem, differential equation does NOT have to be first order linear. There are more than an ODE that works.

Observe that by the trigonometric identity you provided, $$y(x) = \sin(x + \mbox{c}_1) = \cos(\mbox{c}_1)\sin(x) + \sin(\mbox{c}_1)\cos(x)$$

By calculus, we have the following pattern: $$\begin{aligned} y'(x) &= \cos(\mbox{c}_1)\cos(x) - \sin(\mbox{c}_1)\sin(x)\\ y''(x) &= -\cos(\mbox{c}_1)\sin(x) - \sin(\mbox{c}_1)\cos(x)\\ y'''(x) &= -\cos(\mbox{c}_1)\cos(x) + \sin(\mbox{c}_1)\sin(x)\\ y^{(4)}(x) &= \cos(\mbox{c}_1)\sin(x) + \sin(\mbox{c}_1)\cos(x) \end{aligned}$$

So one of the ODEs that works (and also easy to find for this type of problem) is $$y^{(4)} = y$$

Remark: You can also differentiate $y(x) = \sin(x + \mbox{c}_1)$ without using the identity. Using chain rule four times, you get $y^{(4)} = y$.

share|cite|improve this answer
Thank you. I thought it was limited to linear ODE. – SomeGuyOutThere Feb 16 '14 at 17:31
Those are linear. – Paul Safier Feb 16 '14 at 18:32

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.